1998
DOI: 10.1246/cl.1998.765
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitive Oligomer Formation and Laser-induced Polymerization of Aniline on a Gold Electrode Surface: A Surface-Enhanced Raman Scattering Study

Abstract: The process of laser-induced electropolymerization of aniline was studied by in situ surface-enhanced Raman scattering (SERS) spectroscopy and cyclic voltammetry (CV). Formation of p-coupled aniline oligomers was confirmed at an electrode potential below the oxidation potential of aniline, and the oligomers were found to be the source compound for photo-induced electropolymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…For aniline adsorbed on silver and gold, the strongest SERS band was observed at ∼1000 cm −1 , which can be attributed to the v 12 vibration . Although some preternatural bumps appeared at around ∼950 and 1080 cm −1 in the SERS of aniline on silver and gold, respectively, the abnormally enhanced SERS bands were overlooked. Now we assign it to the wagging vibration of the NH 2 group on the basis of our present theoretical calculations.…”
Section: Resultsmentioning
confidence: 96%
“…For aniline adsorbed on silver and gold, the strongest SERS band was observed at ∼1000 cm −1 , which can be attributed to the v 12 vibration . Although some preternatural bumps appeared at around ∼950 and 1080 cm −1 in the SERS of aniline on silver and gold, respectively, the abnormally enhanced SERS bands were overlooked. Now we assign it to the wagging vibration of the NH 2 group on the basis of our present theoretical calculations.…”
Section: Resultsmentioning
confidence: 96%
“…It has been demonstrated that a selective electrochemical manufacture can be realized with the aid of laser and the laser-induced electrochemical polymerization of organic compounds has also been reported [29,[37][38][39]. Therefore, we carried out an experiment to find out whether the laser has an effect on the polymerization of acetylene.…”
Section: Resultsmentioning
confidence: 99%
“…In the SERS spectrum recorded with the gold substrate, many strong bands are found. Because of this difference from the silver spectrum and because Ishioka et al 30 reported a different spectrum, although under different experimental conditions, one can question whether these strong bands are related to reaction products. However, the possibility of oligomer formation followed by photoinduced polymerization can most likely be excluded because of the long wavelength excitation.…”
Section: Nir-sers Spectroscopy Of Triazine Derivatives: Influence Of mentioning
confidence: 99%
“…However, the possibility of oligomer formation followed by photoinduced polymerization can most likely be excluded because of the long wavelength excitation. 30 Alternatively, one can speculate that the strong bands are related to normal modes that involve movement of the atoms of the amino groups and experience the strong enhancement because of the close proximity to the metal surface.…”
Section: Nir-sers Spectroscopy Of Triazine Derivatives: Influence Of mentioning
confidence: 99%